"Dalyellioida" (Platyhelminthes, Rhabdocoela) from the Río de la Plata estuary in Argentina, with the description of two new species of Gieysztoria - Brusa, Francisco; Damborenea, Cristina; Noreña, Carolina (Zootaxa, 2008)
Two new species of Gieysztoria are described, along with the first record of two species of this genus in Argentina. Gieysztoria atalaya n. sp. has a sclerotic stylet with a window on one of its sides and a belt bearing three types of spines. One hollow spine, originated under the window, is basally broad and tapers towards its blunt distal end. This spine separates the other two groups of spines, one of approximately ten thick spines situated on the edge of the belt, and the other arranged in several rows. The proximal row bears approximately 10 triangular spines, broad at the base and rapidly tapering. Gieysztoria matilde n. sp. has a sclerotic stylet with a belt formed by a fibrous framework and a circular window. A central projection arising under this window bears a large blade-shaped hollow spine. This spine separates two major groups of thin spines, one formed by several parallel rows of hollow, acicular, very thin spines, the other comprising hollow and slightly thicker spines with broader base, arranged in several irregular rows. Gieysztoria evelinae (Marcus 1946) Luther 1955, Gieysztoria hymanae (Marcus 1946) Luther 1955 and Gieysztoria falx Brusa, Damborenea and Noreña 2003 are reported for the second time after their original description. Nygulus evelinae Marcus 1954 is cited for the first time for Argentina; until now, this species was known only for the estuary of Itanhaen River in Bahia de Santos, Brazil.